The role of radiographic imaging and finite element analysis in evaluating occlusal loads and stress distribution in the periodontal ligament - Nainggolan, Lidya Irani; Priaminiarti, Menik; Kiswanjaya, Bramma; Iskandar, Hanna Bachtiar (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2024)
Objectives: Biomechanical behavior analysis of the periodontal ligament (PDL) under various loading conditions is essential for understanding the impact of occlusal force distribution. A comprehensive understanding of this aspect is fundamental, and radiographic examination is a crucial modality for evaluating periodontal health. This review aims to illustrate the role of radiographic examination in influencing dental prognosis through the use of Finite Element Analysis (FEA) to assess occlusal load and stress distribution in PDLs. Review: Radiographic imaging techniques are critical for assessing the extent of occlusal trauma and its impact on the periodontal ligament and surrounding structures. Modalities such as conventional radiography, cone-beam computed tomography (CBCT), and micro-computed tomography (micro-CT) are commonly used to evaluate occlusal load. Studies have demonstrated that a balanced occlusal scheme results in a more uniform stress distribution, while an unbalanced scheme leads to localized stress concentrations, increasing the risk of periodontal damage. FEA has emerged as a powerful tool for simulated and visualizing stress patterns in the PDL and quantitatively calculating stresses and deformations in the periodontium. Technological advances in imaging, when applied in conjunction with finite element computational techniques, have shown that oblique loading results in higher stress concentrations compared to vertical loading, particularly in the PDL of mandibular first molars. These higher stresses, often observed in the cervical and apical regions, highlight the potential for more significant PDL damage, making it useful for evaluating bone loss and PDL integrity. for eligibility and completeness of journals. Conclusion: Integration of advance radiographic imaging with FEA has significantly enhanced the understanding of occlusal load and stress distribution in the periodontal ligament. This advancement has propelled the field of periodontal biomechanics, offering very valuable insights into PDL’s biomechanical behavior as it responds to varying occlusal loads, to optimize outcomes in periodontal and orthodontic care.